CUSTOMER TRUST IN E-BANKING DURING COVID-19 PANDEMIC IN BANGLADESH - Chowdhury, Md. Shahnur Azad; Islam, Md. Shahidul; Haque, Md. Shariful; Chowdhury, Mohammad Shyfur Rahman; Hossain, Mohammad Emdad (Indian Journal of Finance and Banking, 2022)
The purpose of this study is to determine the trust that E-Banking customers possess regarding the effect of customer satisfaction, which depends on the E-Banking infrastructure facility and E-Banking Communication environment. Using stratified random sampling in randomized block design, the response to a survey questionnaire has been obtained from 400 respondents via E-mail and hand-to-hand to know their opinion. Structure Equation Model (SEM) with Kolmogorov Smirnov Test, Shapiro Wilk Test, Mann-Whitney Test, Kruskal-Wallis Test, and Least Significant Difference (LSD) tests are used to determine the factors that affect E-Banking customer trust. It is observed, from this study, that an increased E-Banking communication environment, leads to the enhancement of customer satisfaction, as there is a positive significant relationship. Result also shows bachelor's degree and master's degree holder customers exhibit more trust in the E-Banking process than the customers with a lower level of education. Customers who started e-banking transactions during Covid-19 own more trust value than the customers who started transactions before the pandemic. So, the growth of E-Banking transactions may contribute positively to ensuring sound health in the future and especially in any pandemic situation.JEL Classification Codes: G21.